Preparation and Electrochemical Performance Analysis of Flexible Ionic Polymers by Freeze-Drying Technology - Jintao Zhao; Junpeng Shao; Zhenjie Zhang; Bo Liang; Mingchao Yuan; Hanyu Wang (Advances in Materials Science and Engineering)
With the development of bionics and marine science, a new artificial muscle material, IPMC (ion-exchange polymer metal composite), has attracted significant attention. However, the performance issues, as well as problems associated with the preparation of IPMC, have limited its development. In this study, we use the freeze-drying technique, successfully creating a new type of enhanced carbon nanotube IPMC material. Moreover, we also use the method of cyclic voltammetry, ac impedance, and the constant current charge and discharge method to analyze and evaluate the multiwalled carbon nanotube (MWCNT)-reinforced IPMC produced by freeze-drying technology. Freeze-dried IPMC has a higher moisture content, which is 1.58 times higher than that of ordinary IPMC. The pore and multiwalled carbon nanotube (MWCNT) in the ion exchange membrane are distributed more homogeneously. The technology prepared by IPMC has superior electrical performance. Under a 2 v scanning interval and a scanning speed of 50 mV/s, its specific capacitance can reach 247.5335 mF/cm−2, which is 24 times that of normal IPMC. Under the same conditions, its conductivity can reach 0.29391 mS/cm, far higher than that of ordinary IPMC. Furthermore, the preparation process is also safer. This method provides a new strategy for the future preparation and usage of IPMC.